Perancangan Ulang Tata Letak Fasilitas Dengan Metode Blocplan Pada CV. Anugrah Masruroh Teknik - Muhammad Jordan Samudra Putra; Renanda Nia Rachmadita; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
In a company, the arrangement of machinery and equipment affects production activities, especially the effectiveness of the production process time and the fatigue experienced by operators on the production floor. A good layout is a layout that is arranged based on the flow pattern of materials and equipment that is regular and effective. Based on observations made at CV. Anugrah Masruroh Teknik, the problem in this business is the placement of facilities that hinder the process of moving materials. The location of receiving materials inhibits the process of moving materials from one machine to another. This study aims to obtain a better layout to minimize the distance or minimize the distance of movement between production stations. The method used in this research is BLOCPLAN (Block Layout Overview with Computerized Planning Using Logic and Algorithms). The resulting 5 alternative layouts can be made which are then selected to determine the most efficient alternative layout based on the smallest material handling costs. The results showed an alternative layout resulting from the BLOCPLAN method with a minimization of the distance between facilities of around 68.5% and a reduction in material handling costs of around 68.3% of the actual layout. The redesign of the production facility layout of CV Anugrah Masruroh Teknik is considered effective using the BLOCPLAN method.